2016
DOI: 10.1002/pola.28230
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and UCST-type phase behavior of polypeptide with alkyl side-chains in alcohol or ethanol/water solvent mixtures

Abstract: A series of thermoresponsive polypeptides bearing 1‐butyl, 1‐hexyl, or 1‐dodecyl side‐chains (i.e., 6a‐6c) were synthesized by copper‐mediated 1,3‐dipolar cycloaddition with high grafting efficiency (>95%) between side‐chain “clickable” polypeptide, namely poly(γ‐4‐(propargoxycarbonyl)benzyl‐L‐glutamate) (5) and 1‐azidoalkanes. 5 with different degree of polymerization (DP = 48–86) were prepared from triethylamine initiated ring‐opening polymerization of γ‐4‐(propargoxycarbonyl)benzyl‐L‐glutamic acid based N‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 52 publications
5
17
3
Order By: Relevance
“…OEGylated polypeptides (P1‐OEG x and P2‐OEG x , x = 3, 7) with different hydrophobic linkage groups (phenyl linkage for P1‐OEG x and benzoic acid phenyl ester linkage for P2‐OEG x ) and various OEG pendants were designed to achieve thermoresponsive polypeptides with a lower critical solution temperature (LCST)‐type solution phase transition temperature ( T pt ) at around body temperature. P1 (Scheme ) was prepared according to a reported procedure using Et 3 N as the initiator . The molecular structures of the monomer and P1 were confirmed by 1 H NMR spectroscopy (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…OEGylated polypeptides (P1‐OEG x and P2‐OEG x , x = 3, 7) with different hydrophobic linkage groups (phenyl linkage for P1‐OEG x and benzoic acid phenyl ester linkage for P2‐OEG x ) and various OEG pendants were designed to achieve thermoresponsive polypeptides with a lower critical solution temperature (LCST)‐type solution phase transition temperature ( T pt ) at around body temperature. P1 (Scheme ) was prepared according to a reported procedure using Et 3 N as the initiator . The molecular structures of the monomer and P1 were confirmed by 1 H NMR spectroscopy (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The solubility difference in MeOH for P1‐OEG 7 and P2‐OEG 7 was ascribed to the hydrophobicity increase in P2‐OEG 7 . The mechanism of UCST‐type solution phase transition in alcohols is that polymers tend to aggregated at low temperatures, but H‐bonding interactions between the polar linkages (e.g., ester bonds and 1,2,3‐triazole groups) and OEG groups of polymers and alcoholic molecules increased as temperature elevation, resulting in polymer dissolution …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work have suggested that thermoresponsive polymers with UCST‐type phase behaviors in alcoholic solvents also showed UCST‐type phase behaviors in alcohol/water binary solvent mixtures . Therefore, the solubility of the resulting polypeptides in MeOH/H 2 O or EtOH/H 2 O binary solvent mixtures has also been tested.…”
Section: Resultsmentioning
confidence: 99%